Sanitation and Hygiene Monitoring System for Preventing Viral Infections in Orphanage Homes - Aina, Victoria Olusayo; AKPOR, Oluwaseyi Abiodun; Ekundina, Victor olukayode; Afolalu, Adeniran Sunday (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Maintaining proper sanitation and hygiene is crucial in preventing the spread of viral infections, especially in high-risk environments such as orphanage homes, where many children live in close proximity and have limited access to healthcare Maintenance of adequate sanitation and hygiene is significant in the prevention of the spreading of viral infection, particularly in high-risk environments like orphanage homes, where several children live closely and having limited access to healthcare. Thus, the review presents the forensic overview of how to the design process and standards of Smart Sanitation as well as Hygiene can help to reduce the risk of viral infections in orphanage facilities. From the results of the reviewed literatures, it was observed that adequate smart homes for the orphanage will require smart monitoring using internet of things and data analytics with certain parameters like level of compliance to hand washing, air quality, cleanliness of the rest room and usual disinfection of surfaces. Thus, real-time data help givers and administrators to take proactive action each time the hygiene level fall below standard. Furthermore, the system will have to include reports and educational guidelines for the purpose of reinforcing the practice of hygiene. Therefore, the study provides a great insight by establishing that leveraging on technology will help to develop a healthier environment, reduce the outbreak of infections while supporting the wellbeing of vulnerable children in the orphanages.